School principals apply total quality management in the al-Batinah north governorate in the Sultanate of Oman and its impact on teacher performance = تطبيق مديري المدارس لإدارة الجودة الشاملة في محافظة شمال الباطنة بسلطنة عمان وأثرها على أداء المعلمين - Insaf Mohammed Said, Insaf Mohammed Said; Amzat, Ismail Hussein (International Organization Center of Academic Research (OCERINT), 2020)
This study aimed to find out the application of school principals for total quality management in the North Al Batinah Governorate and its impact on the performance of teachers. The study population )consisted of 10390 teachers, and the study sample was chosen( )from 450 teachers from the schools in the North Al Batinah( Governorate, in a randomized probabilistic way, The study adopted the quantitative approach, using the Smart PLS program, through confirmatory factor analysis and path analysis, and used a developed tool for measurement, according to the study goals and reached the following results, that the application of school management to total quality management, a positive impact on the performance of teachers, has been presented a number of Recommendations based on the results of the study. ******************************************************************************* هدفت هذه الدراسة لمعرفة تطبيق مديري المدارس لإدارة الجودة الشاملة في محافظة شمال الباطنة واثرها في على أداء المعلمين، وتكون مجتمع الدراسة من (10390) معلمًا ومعلمة، واختيرت عينة الدراسة من (450) معلم ومعلمة، من مدارس محافظة شمال الباطنة، بالطريقة الاحتمالية العشوائية، واعتمدت الدراسة المنهج الكمي، باستخدام برنامج، من خلال التحليل العاملي التوكيدي، وتحليل المسار، واستخدمت أداة مطورة للقياس، وفقا لأهداف الدراسة وتوصلت للنتائج الآتية، أن لتطبيق الإدارة المدرسية لإدارة الجودة الشاملة، تأثير إجابي على أداء المعلمين، وقد تم تقديم عدد من التوصيات بناء على نتائج الدراسة .